STRATEGI BISNIS RITEL DALAM MEMPERTAHANKAN PERSAINGAN YANG KOMPETITIF KEPADA PEMILIK TOKO RITEL - Prikurnia, Anas Khair; Adriani, Weni Yunisa (Institut Teknolog dan Bisnis Diniyyah Lampung, 2024)
ABSTRACT This research activity was conducted for retail store owners in Natar Village, South Lampung Regency. The outcomes of this activity are: 1) Increased knowledge and insights of the participants in maintaining retail businesses in the face of competitive challenges, 2) Enhanced participant knowledge in business management, where owners must be able to separate roles in financial management, operational management, human resource management, and marketing management to ensure their businesses remain sustainable, 3) Improved participant knowledge in online marketing, enabling direct delivery of goods to stores, 4) Continuation of this activity, fostering a partnership principle between the outreach team and the retail store owners. The activity was carried out through the following stages: 1) Selection of community outreach participants, specifically retail business owners in Natar Village, South Lampung Regency, 2) Presentation of outreach materials on strategies to sustain retail businesses in a competitive environment, 3) Conducting evaluations. The evaluations were done by: pre-outreach, conducting a Q&A session to assess each participant's initial knowledge of the retail business; post-outreach, conducting another Q&A session on the same material. By comparing the results, it will be determined whether there is an increase in participant knowledge about retail business management and its scope. Keywords: strategy, retail business, competitive environment